Restaurant food waste management strategy in Asia using the Restaurant Food Waste Map (RFWM) approach - Fajriah Elsa; Martianto Drajat; Hustina Rachman Purnawati (BIO Web of Conferences)
Background: Food waste is a global issue due to its serious environmental, economic, and social impacts. Objective: This research aimed to collect information regarding restaurant food waste management using the Restaurant Food Waste Map (RFWM) approach. Method: This research is a narrative review. Results: The main contributors to food waste at each phase are managers, chefs, kitchen staff, waiters, and customers. Most types of food waste produced are avoidable. Factors that influence food waste include management of food supplies, serving styles, and customer behaviors. Conclusion: Management strategies that can be implemented include improving food supply management, using smaller plates, and various interventions to increase customer awareness of food waste.